Evaluating the effects of road hump on speed and noise level at a university setting - Mustafa, Nur Asiah; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2019)
This study is carried out to determine the effectivness of road humps to reduce the traffic speed and traffic noise in institutional area. The difference in hump profiles in terms of height, width and length are the main factors in determing the effectiveness of road humps. The difference in the profiles of the road hump will cause changing driver behaviour of the users especially when approaching the road hump. The road humps with different design profiles are selected to measure the speed and noise level of the vehicles at, before and after each of the selected road humps. Radar speed gun and noise level meters are used to measure speed and noise level of the vehicles at each of designated points along the major circular road in IIUM. The changes in speed and noise level at different selected points at each of the different profiles of the road humps are the expected findings of this study.